Низкотемпературное (менее 1100ºС) испарение кремния и углерода - Харламов, А. И.; Кириллова, Н. В.; Карачевцева, Л. А.; Головкова, М. Е.; Каверина, С. Н.; Фоменко, Вениамин Васильевич (My University, 2004)
Исследовано взаимодействие порошков кремния и углерода на поверхности пластинки кремния и микрофибры углерода. Впервые наблюдалось образование карбида кремния за счет интенсивного испарения кремния и углерода около 1000ºС с параллельной екзотермической реакцией образование карбида кремния.

The interactions of porous silicon plate and a carboneous microfiber with powdery carbon and silicon, respectively, are examined. It is first shown that the joint evaporation of silicon and carbon is enough intense at temperatures close to 1000oC owing to the parallelly running exothermic reaction of the formation of silicon carbide from evaporated atoms of Si and C. A growth of thread-like silicon carbide including that the pores (a diameter of up to 50 µm) of a thin plate made of monocrystalline silicon which is placed into a carbon powder is occurred through the interaction of evaporating reagents at a local high-temperature center.
Keywords: кремний; углерод; испарение; синтез; порошки; silicon; carbon; evaporation; powder; sinthesys; кафедра харчової хімії